(untitled) (Indian Journal of Arid Horticulture, 2021)
An experiment was conducted during 2016-17 at Main Experiment Station, N.D. University of Agriculture & Technology, Kumarganj, Faizabad (U.P,) to study the physico-chemical attributes of ber fruit cv. Banarasi Karaka. The experiment comprised of three replications with seven treatments in RBD viz. T1 (Control), T2 (100% RDF through NPK),T, (100% FYM), T, (50% FYM +50% RDF through NPK), T, (50% FYM +50% (PSB+Azotobacter), T, (75% FYM +25% RDF through NPK), T, (75% FYM + 25% RDF through NPK + 25% (PSB + Azotobacter). Therefore, it may be recommended application of treatment T, is (75% FYM + 25% RDF through NPK + each 25% PSB + Azotobacter) to ber growers for obtaining larger and heavier ber fruit followed by application of 50% RDF through FYM +50% RDF through NPK.